Perbandingan Efektivitas Mindfulness Based Intervention Terhadap Diabetes Resilience Training pada Diabetes Burnout Syndrome dan Kontrol Glikemik Penderita Diabetes Melitus Tipe 2 - Made Dian Kusumawati; Kusnanto Kusnanto; Bambang Purwanto (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Introduction: Diabetes burnout is a major challenge in the management of Diabetes mellitus. It can lead the patient to an uncontrolled blood sugar situation, which ends up in an increased mortality rate caused by Diabetes complications. The aim of this study was to compare the effectiveness of a mindfulness-based intervention to diabetes resilience training on diabetes burnout syndrome and glycemic control in type 2 diabetes mellitus patients. Methods: Eight databases were systematically searched namely Scopus, ProQuest, PubMed, Science Direct, EBSCO, SINTA, Springer Link, and Google Scholars, using a randomized controlled trial or quasi-experimental design, published between 2011-2021 with the combinations of 6 groups of keywords in English and Bahasa Indonesia limited articles. Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines and JBI’s checklist were followed during all stages of this review. The researcher independently assessed the eligibility of the studies by title, abstract, full-text, and the methodological quality of the studies. Data tabulation and narrative analysis of study findings were performed. Results and Analysis: A total of 25 studies were satisfied the inclusion criteria and have been included in this review. Of the studies reviewed, 3549 participants included were T2DM patients undergoing Diabetes treatments for more than 6 years. Of the 12 mindfulness-based studies, 7 studies showed a significant effect. Meanwhile, in diabetes resilience training, 8 out of 13 studies showed a significant effect on both outcomes. The significance of the results in both interventions as indicated by the p-value < 0 .05 Discussion: Mindfulness reducing depression by increasing the volume and density of the gray areas of the brain which previously decreased due to stress or depression. Meanwhile, diabetes resilience training works by increasing cognitive, social, and effective brain coping functions in the hippocampus and prefrontal cortex areas, so that respondents become more aware of their self-management and glycemic control. Conclusion: Both interventions are effective in reducing diabetes burnout/depression. But diabetes resilience training is more effective if given in early diabetes conditions because the knowledge gained will help respondents to be aware of their self-management and glycemic control earlier.Keywords: diabetes burnout syndrome; glycemic control; mindfulness; diabetes resilience trainingABSTRAK Pendahuluan: Diabetes burnout merupakan tantangan utama dalam pengelolaan Diabetes mellitus. Hal ini berdampak pada tidak terkontrolnya gula darah pasien, yang berakhir dengan peningkatan angka kematian disebabkan oleh komplikasi Diabetes. Tujuan dari penelitian ini adalah untuk membandingkan efektivitas intervensi berbasis mindfulness dengan diabetes resilience training terhadap diabetes burnout dan kontrol glikemik penderita DMT2. Metode: delapan database dicari secara sistematis meliputi: Scopus, ProQuest, PubMed, Science Direct, EBSCO, SINTA, Springer Link, dan Google Scholars, menggunakan Randomized Controlled Trial atau desain kuasi eksperimen, diterbitkan antara tahun 2011-2021 dengan kombinasi 6 kelompok kata kunci dalam bahasa Inggris dan bahasa Indonesia. The Joanna Briggs Institute Guideline digunakan untuk menilai kualitas studi, sedangkan PRISMA checklist digunakan sebagai panduan dalam membuat review. Peneliti secara independen menilai kelayakan penelitian berdasarkan judul, abstrak, teks lengkap, dan kualitas metodologi penelitian. Data diekstraksi, ditabulasi, dan analisis naratif dari temuan studi ditampilkan serta dirangkum secara singkat. Hasil dan analisis: sebanyak 25 studi memenuhi kriteria inklusi dan telah dimasukkan dalam tinjauan ini. Dari seluruh studi yang ditinjau, 3549 responden adalah pasien DMT2 yang menjalani perawatan diabetes selama lebih dari 6 tahun. Dari 12 studi berbasis mindfulness, 7 studi menunjukkan efek yang signifikan. Sementara itu, dalam studi diabetes resilience training, 8 dari 13 studi menunjukkan efek yang signifikan pada kedua outcomes. Signifikansi hasil pada kedua intervensi ditunjukkan dengan p-value < 0,05. Diskusi: mindfulness menurunkan depresi dengan meningkatkan volume dan kepadatan area abu-abu otak yang sebelumnya menurun karena stres atau depresi. Sementara itu, diabetes resilience training bekerja dengan meningkatkan fungsi kognitif, sosial, dan koping otak di area hipokampus dan korteks prefrontal, sehingga responden menjadi lebih sadar akan manajemen diri dan kontrol glikemik mereka. Kesimpulan: kedua intervensi efektif dalam menurunkan burnout/depresi diabetes. Namun, diabetes resilience training lebih efektif jika diberikan pada kondisi awal diabetes karena pengetahuan yang diperoleh akan membantu responden untuk menyadari manajemen diri dan kontrol glikemiknya lebih dini.Kata kunci: diabetes burnout syndrome; kontrol glikemik; mindfulness; diabetes resilience training